Frequency Analysis of Transients in Electrochemical Noise of Superalloys Waspaloy and Ultimet - Jáquez Muñoz, Jesús Manuel; Gaona Tiburcio, Citlalli; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Olguín Coca, Javier; Estupiñan López, Francisco Humberto; López León, Luis Daimir; Chacón Nava, José G.; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2021)
Nickel or Cobalt-based superalloys represent an important class of engineering materials, finding widespread application in critical components within the gas turbine engines used for jet propulsion and electricity generation. This research aimed at the frequency analysis of transients in electrochemical noise of Waspaloy and Ultimet superalloys, immersed in 3.5 wt.% in H2SO4 and NaCl solutions at two different temperatures, 25 and 60 °C. Localized corrosion behavior of superalloys was assessed using the electrochemical noise technique (EN) according to ASTM-G199 standard. Three different statistical methods filtered the EN signal, and the polynomial method was employed to obtain the noise resistance (Rn), the localization index (LI), skew and kurtosis, and the power spectral density analysis (PSD). Results indicate that the current and potential noise transients have a better behavior with better clarity when a polynomial is used to show a localized corrosion kurtosis for both superalloys.